Transferosomes: A Next-Generation Ultra-Deformable Vesicular System Structure, Mechanism, and Future Prospects - Sameer Shafi; Shivlila Swami; Pranita Waghmare; Ankita Gadhave; Madhuri Damane (Asian Journal of Pharmaceutical Research and Development, 2025)
Targeted Drug Delivery Systems (TDDS), also known as smart drug delivery systems, are designed to increase drug concentration at specific target sites while minimizing systemic exposure. Among various vesicular carriers, transferosomes have emerged as highly effective for dermal and transdermal drug delivery. Transferosomes are ultra-deformable vesicles composed of phospholipids and edge activators that enable them to penetrate the stratum corneum through narrow pores, driven by the osmotic gradient between skin layers. Their unique elasticity and hydration-driven mobility facilitate enhanced permeation and controlled drug release.Transferosomes can encapsulate both hydrophilic and lipophilic drugs, providing high entrapment efficiency, biocompatibility, and biodegradability. They improve bioavailability, reduce first-pass metabolism, and minimize toxicity. However, high production costs, formulation instability, and phospholipid purity issues remain significant challenges.Several preparation techniques, including thin-film hydration, rotary evaporation, and ethanol injection, yield vesicles with desirable size and stability. Characterization involves determining entrapment efficiency, vesicle morphology, zeta potential, in vitro release, and skin permeation. Transferosomes have been successfully employed in delivering anticancer agents, proteins, peptides, insulin, corticosteroids, and antifungal drugs with enhanced therapeutic outcomes.Despite certain drawbacks, transferosomes represent a promising and versatile carrier for non-invasive and site-specific drug delivery. Their superior permeability, controlled release, and compatibility with both synthetic and natural drugs make them a significant advancement in transdermal nanocarrier systems.